Field work in geographical education in Slovenia - Konečnik Kotnik, Eva; Žiberna, Igor (Journal for Geography, 2025)
As a form of direct engagement with the subject of geographical study—the landscape—field work holds significant importance both in research and educational contexts. This applies to geographical research, academic study of geography, and across various educational levels. This article defines the broader educational contexts of geographical field work, presenting its prevalence in primary, secondary, and tertiary geographical education in Slovenia. Drawing on empirical research into the actual curriculum, it describes geography teachers’ perceptions of field work, its benefits, challenges in implementation within the (geographical) educational process, and other practical considerations of its execution.